Embattled Europe : a progressive alternative - Jarausch, Konrad H. (Konrad Hugo), 1941- (Princeton University Press, 2021)
"Over the past decade, Euroskepticism has been on the rise, with many predicting the end of the European Union and the failure of progressive European values. With Brexit on the horizon, the far-right in power in Poland, authoritarianism on the rise in Hungary, riots in Paris, and austerity policies in place across the continent, it often seems that there is little reason to be optimistic about Europe's future or proud of its recent past. Konrad Jarausch begs to differ. In this book, which he will write as a Tony Judt-style extended essay, he traces the history of Europe since 1989 and finds much cause for hope. Despite the Greek debt crisis, the weak reaction to the Russian invasion of Eastern Ukraine, and other failures that Euroskeptics cite frequently, the European model is strong. Jarausch ends his narrative by pointing to successes, such as Danish efforts to combat global warming, Sweden's restructuring of its welfare system, and Spain's transition to democracy and its ability to cope with a large influx of immigrants, among many other issues. Though Europe has many challenges to overcome in the next few decades, it still presents a powerful alternative to American-style unbridled capitalism and right-wing populism. Jarausch will color his narrative with his own impressions of living in both Europe and the United States at various points during this period"-- Provided by publisher.
Keywords: Europe -- History -- 1989-; Europe -- Politics and government -- 20th century.; Europe -- Politics and government -- 21st century.; Europe -- Social conditions -- 20th century.; Europe -- Histoire -- 1989-; Europe -- Politique et gouvernement -- 20e siècle.; Europe -- Politique et gouvernement -- 21e siècle.; HISTORY / Europe / General.; SOCIAL SCIENCE / Regional Studies.; Politics and government; Social conditions; Europe; Since 1900; History